Volume 5: Turbo Expo 2003, Parts a and B 2003
DOI: 10.1115/gt2003-38340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotation on Heat Transfer in Narrow Rectangular Cooling Channels (AR = 8:1 and 4:1) With Pin-Fins

Abstract: The effect of rotation on smooth narrow rectangular channels and narrow rectangular channels with pin-fins is investigated in this study. Pin-fins are commonly used in the narrow sections within the trailing edge of the turbine blade; the pin-fins act as turbulators to enhance internal cooling while providing structural support in this narrow section of the blade. The rectangular channel is oriented at 150° with respect to the plane of rotation, and the focus of the study involves narrow channels with aspect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…In an experiment conducted by Wright et al [13], the level of heat transfer in a rotating channel with staggered arrays of the pin-fin type was higher than that in the stationary case. They found that rotation enhanced heat transfer from all heated surfaces, especially on the trailing surface.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…In an experiment conducted by Wright et al [13], the level of heat transfer in a rotating channel with staggered arrays of the pin-fin type was higher than that in the stationary case. They found that rotation enhanced heat transfer from all heated surfaces, especially on the trailing surface.…”
Section: Introductionmentioning
confidence: 92%
“…1a, are considered to investigate the enhancement of heat transfer. The experimental test channel of Wright et al [13] consisted of 12 rows of pin fins arranged in staggered arrays on heated walls. In this work, however, a domain with only the first six rows of pin fins in the test channel of Wright et al [13] is considered in the computational domain, as shown in Fig.…”
Section: Numerical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that pin fins significantly reduce the effect of rotation, but they do not eliminate the effect. Wright et al [14] studied a staggered array of pins under the rotating condition and found that 1) rotation enhances the heat transferred from the pin-fin channels 1.5 times that of the stationary pin-fin channels. 2) Overall, rotation enhances the heat transfer from all surfaces in both the smooth and pin-fin channels.…”
mentioning
confidence: 98%